VD_FINDINFO Jug / 2016 / 362 vom 25. April 2016 - VD Tribunal cantonal (2016)
CONCOURS D'INFRACTIONS, LOI FÉDÉRALE SUR LA CIRCULATION ROUTIÈRE, DROIT DE GARDER LE SILENCE | 43 CP, 90 LCR, 113 CPP (CH), 168 CPP (CH)